Ultrasonography in the Assessment of Tumors of the Cheek: Water Mouth Distension Technique - Chammas, Maria Cristina; Takahashi, Marcelo Straus; Moyses, Raquel Ajub; Pompeia, Celine; Tavares, Marcos Roberto; Cerri, Giovanni Guido (Ultraschall in der Medizin - European Journal of Ultrasound, 2022)
Purpose To describe a new B-mode ultrasound examination technique to assess cheek tumors.Materials and Methods 30 cheek oral cavity lesions of different histological types (11 benign and 19 malignant) from 23 patients (11 women and 12 men, 7–82 years old, mean age of 49.5 years) were analyzed. Transcutaneous oral B-mode ultrasound (5–12 MHz transducer) was carried out in two stages. Initially it was performed conventionally with an empty mouth. Next, the patient was asked to keep their oral cavity filled with water (like when using a mouthwash) during imaging for the new test examination technique. The anatomical layers of this region and the characteristics of the tumors were evaluated. Lesions were classified as ill defined, partially defined, or defined. Conventional findings were compared to those of the new technique using the Wilcoxon signed-rank test. Ultrasound results were compared to histological findings analyzed by an independent team.Results The conventional empty mouth technique was able to confidently define lesion extension in only 6 of the 30 lesions, while the water-filled mouth technique was able to confidently define lesion extension in 29 of the 30 lesions (p<0.00001).Conclusion We present a novel technique that dramatically improves ultrasound staging of cheek oral cavity tumors. In addition to the increase in ultrasound accuracy, this technique does not require any special equipment or extra cost, is very well tolerated by patients, and thus should be considered in the evaluation of every patient undergoing transcutaneous cheek ultrasound for oral cavity lesion characterization.
Keywords: B-mode ultrasound; cheek diagnostic imaging; mouth neoplasm; oral cancer; cheek tumor